Constructing desirable ion-conducting channels within ionic liquid-based composite polymer electrolytes by using polymeric ionic liquid-functionalized 2D mesoporous silica nanoplates. (March 2017) - Wang, Shun; Shi, Qing Xuan; Ye, Yun Sheng; Xue, Yang; Wang, Yong; Peng, Hai Yan; Xie, Xiao Lin; Mai, Yiu Wing
Abstract: The structural design of ion-conducting channels within polymer electrolytes (PEs) is of prime importance if their transport properties, especially in high performance electrochemical devices, must be optimized. Although many efforts have been directed towards enhancing the transport properties of PEs through nanoscopic modification, few investigations have successfully used nanofillers to achieve enhanced target ion conduction in composite polymer electrolytes (CPEs). In this work, we show that the transport properties of polymeric ionic liquid (PIL)-based PEs can be optimized by the incorporation of 2D silica nanofillers and that desirable transport properties result from the inclusion of abundant, shorter, continuous and interconnected ion transfer pathways created by a combination of grafted PIL and mesoporous structures in 2D silica nanofillers. The presence of PIL-functionalized mesoporous silica nanoplates (PIL-FMSiNP) increases the ionic conductivity of PIL/IL PEs by 1130% at room temperature (~30 °C) while significantly decreasing the ion transport activation barrier (ca. 10 kJ mol −1 ). Such nanofillers simultaneously confer both high ionic conductivity [(~10 −3  S cm −1 at 130 °C) with only a small amount of IL loading (15 wt%)], and excellent IL immersion and retention properties to PIL/IL PE. The CPE's favorable transport properties make it well-suited for the fabrication of electrochemical devices including Li batteries, fuel cells, dye-sensitized cells, and supercapacitors. Preliminary Li battery tests have shown that Li/LiFePO4 cells with PIL/IL/PIL-FMSiNP CPE are capable of delivering 135.8 mA h g −1 capacity at 60 °C during 30 charge/discharge cycles, suggesting that their capacity and capacity retention are superior to cells using unmodified PIL/IL PE (50.0 mA h g −1 ). Graphical abstract: The transport properties of polymeric ionic liquid (PIL)-based PEs can be optimized by the incorporation of 2D silica nanofillers and that desirable transport properties result from the inclusion of abundant, shorter, continuous and interconnected ion transfer pathways created by a combination of grafted PIL and mesoporous structures in 2D silica nanofillers. Highlights: 2D nanoplates within porous structures create 3D ion conductive network that increase ion mobility and lead to high ionic conductivity. The surface porosity of 2D nanofillers in combination with a PIL grafting improves the CPEs' IL immersion and retention properties. Optimized CPEs exhibit high ionic conductivity, which is on the same order of magnitude as that offered by other reinforced CPEs, while only requiring a small IL loading. Li/LiFePO4 cells with PIL/IL/PIL-FMSiNP CPE are capable of delivering high capacity during charge/discharge cycles.